Unexpected cause of headache in a patient with Noonan syndrome: aseptic meningitis - Hacer Efnan Melek Arsoy; Öner Özdemir; Ümmügülsüm Dikici; Ece Tüsüz Önata; Recep Polat (Alergologia Polska)
Malignancies, autoimmune diseases, viral and fungal infections, as well as aseptic meningitis due to certain drugs are frequently seen. Antibiotics, intravenous immunoglobulin (IVIG), non-steroidal anti-inflammatory drugs are often considered responsible. The incidence following IVIG infusion is 0.067%; however, symptoms may start to show up anywhere from 6 h to 4 days following infusion. It is challenging to diagnose and is easily overlooked because of symptoms and clinical findings that might arise from a variety of conditions, including headaches, stiff necks, and vomiting. We present a patient with Noonan syndrome who was diagnosed with common variable immunodeficiency due to recurrent illness, had IVIG replacement therapy, and developed aseptic meningitis following the initial course of treatment. No similar case has been documented before in the literature. Noonan syndrome may also be related with an increased incidence of IVIG-associated aseptic meningitis, while the explanation for this association is unclear.